Two new species of Atlantocuma (Crustacea: Cumacea), and a new genus and species from Japan, Northwest Pacific, with observations on the degeneration of mouthparts in ovigerous females - Akiyama, Tadashi (Zootaxa, 2012)
Two species of the cumacean genus Atlantocuma from the southern coast of Honshu, Japan, 781–861 m depth, A. gamoisp. nov. and A. ojii sp. nov., and Pseudopicrocuma japonicum gen et sp. nov. from Nansei Islands, 566–1769 m depth,are described. Atlantocuma gamoi is characterized by (1) carapace elevated in preparatory and ovigerous female, (2)antero-lateral angle of carapace with 3 teeth in females, and (3) pseudorostrum of carapace of adult males truncate,anterolateral angle without teeth. Atlantocuma ojii is characterized by (1) carapace not elevated in preparatory females,but elevated in ovigerous females, (2) inferior margin of carapace in ovigerous female serrated for entire length, (3)pseudorostrum of carapace in adult males truncate, (4) uropod exopod with 1–2 spiniform setae on inner margin, exceptfor subterminal one. The new genus Pseudopicrocuma, which is similar to Picrocuma from shallow waters of easternAustralia, is characterized by (1) well-developed exopods present on maxilliped 3 and pereopods 1–3 in both sexes, (2)antenna 1 of adult males with many aesthetascs-like sensory setae on peduncle articles 2 and 3, (3) male antenna 2 ofclasping form, and (4) uropod slender, peduncle shorter than rami. Pseudopicrocuma shows affinity to Atlantocuma exceptfor (1) arrangement of well-developed exopods on pereopods, (2) male antenna 2 flagellum of clasping form, and (3)uropod peduncle shorter than rami. In addition, P. japonicum and the new Japanese Atlantocuma species are characterizedby a similar trend in degeneration of mouthparts (mandibles – maxillipeds 2) in ovigerous females, suggesting a ratherclose relationship of these genera with quite different arrangements of exopods on pereopods. These 2 genera are currentlyplaced in Nannastacidae. Other possible relatives of Pseudopicrocuma are Spilocuma (Bodotriidae) and Claudicuma (Nannastacidae).